HORSERADISH PEROXIDASE (HRP) ACTIVITY OF ARMORACHIA LAPATHIFOLIA SUBCULTURED CALLUS IN SOLID AND LIQUID MEDIA - Budiwati, Thelma A.; Pudjiraharti, S.; Karossi, A.T. (LIPI Press, 2009)
Peroxidase is an enzyme which catalyzes the oxidation of organic compound done by peroxide. The peroxidase enzyme can be produced by plants or microorganisms. One of the peroxidase enzymes is Horseradish Peroxidase (HRP). This commercial, HRP is produced through the extraction of Horseradish root (Armorachia lapathifolia) besides it can also be produced through tissue culture. The callus induction was carried out in Linsmaier-Skoog media containing naftalen acetic acid (NAA) and benzyl amino purin (BAP) as the growth hormone. Incubation was conducted at room temperature (2428oC) without lighting anymore for three weeks, At the age of three weeks some of the calli were subcultured in solid media, and the rests were subcultured in liquid media containing growth hormone NAA and kinetin. Incubation was in a shaking incubator at 120 rpm, without light, at the room temperature for 40 days. The sampling was conducted every 10 days. The results of the research showed that the 8th (SC8) and the 10th (SC10) subcultures produced the highest extracellular and intracellular enzyme activity at the age of 20 and 30 days. The extracellular enzyme activity was 38.06 U/ml with specific activity 22.36 U/mg protein and the total activity of 79.92 U. While the intracellular enzyme activity was 253,82 U/g callus, with specific activity of 39.05 U/mg protein and total activity of 649.77 U.